Normative Analysis of Unlawful Acts in the Context of Inhibition of the Certificate Name Reversal Process - Jatmiko, Wisnu; Yuniarlin, Prihati (Walisongo Law Review (Walrev), 2023)
This paper discusses illegal acts that hinder the process of turning over the certificate's name. An unlawful act can be categorized as an unlawful act if the act causes harm to other parties. There are two kinds of losses incurred by unlawful acts, namely material losses, and immaterial losses. With a normative approach, this article finds that an act is categorized as an act against the law if it meets the five elements of an unlawful act. Unlawful acts committed by the seller if based on the Cilacap District Court Decision number 25 / Pdt.G / 2017 / PNClp, namely the existence of an act (the act of buying and selling land), an unlawful act (reselling the object of sale and purchase and delaying the process of returning the name of the certificate), victim losses (immaterial losses), a causal relationship between the act and losses (defendants whose whereabouts are unknown),  the offender's fault (reselling the object of buying and selling land). Thus, the author agrees with the judge of the Cilacap District Court that the lawsuit over the dispute is an illegal act.Tulisan ini membahas tentang perbuatan melawan hukum yang timbul dalam menghambat proses balik nama sertifikat. Suatu perbuatan melanggar hukum dapat dikategorikan sebagai perbuatan melawan hukum apabila perbuatan tersebut menimbulkan kerugian bagi pihak lain. Ada dua macam kerugian yang ditimbulkan oleh perbuatan melawan hukum yaitu kerugian materiil dan kerugian immaterial. Dengan pendekatan normatif, artikel ini menemukan bahwa suatu perbuatan dikategorikan sebagai perbuatan melawan hukum jika memenuhi lima unsur perbuatan melawan hukum. Perbuatan melawan hukum yang dilakukan oleh penjual jika berdasarkan pada Putusan Pengadilan Negeri Cilacap nomor 25/Pdt.G/2017/PNClp yaitu adanya Suatu perbuatan (perbuatan jual beli tanah), perbuatan melawan hukum (menjual kembali objek jual beli dan menunda proses balik nama sertifikat), kerugian korban (kerugian immaterial), hubungan kausalitas antara perbuatan dengan kerugian (tergugat yang tidak diketahui keberadaanya), kesalahan pelaku (menjual kembali objek jual beli tanah). Dengan demikian, penulis sependapat dengan hakim Pengadilan Negeri Cilacap bahwa gugatan atas sengketa tersebut termasuk perbuatan melawan hukum